Utility under the Dark Tetrad - Gomes, Orlando (2025)
Purpose: Literature on psychology highlights four traits that shape an amoral and antisocial personality: Machiavellianism, narcissism, psychopathy and sadism. Together, these personality traits form the Dark Tetrad. In this study, the standard intertemporal utility maximization model is reassessed from the point of view of a representative economic agent endowed with the Dark Tetrad personality traits. Design/methodology/approach: The approach followed in this paper consists of identifying how each of the Dark Tetrad traits might be logically associated with the dynamic utility problem, as well as exploring, in the context of the model, the implications, for consumption and utility, of admitting the presence of such traits in individuals’ personalities. Findings: It is found that, typically, dark personalities penalize consumption growth, even when such traits are interpreted directly and positively contributing to the utility of the agent. It is also found that in economies with two or more interacting agents, the dark traits might have a mutually destructive nature. Originality/value: Economics is going through a smooth revolution in the direction of becoming an eminently behavioral science. Most of the traditional economic models, based on the idea of the hyper-rational agent, are being replaced or complemented by a different view of the homo-economicus, in which, among other things, personality matters. This paper offers a novel contribution in this direction.